A study on Campylobacter jejuni cross-contamination during chilled broiler preparation - M. R., Usha; Robin, Tunung; Chai, Lay Ching; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Studies indicate that bacterial cross-contamination occurs during food preparation where bacteria can retent on the food contact surfaces and cause illness. The study evaluated the adherence of Campylobacter spp. to cutting boards, blades of knives and hands after cutting chilled, raw broiler parts (thighs + drumsticks, wings and livers). The adherence to cucumber cuts that were cut using the unwashed boards and knives was also analyzed. Generally, utensils have higher mean of Campylobacter spp. retained to them (1.4-223.3 MPN/ml rinse) than hands (0.7-43.4 MPN/ml rinse); however, Mann-Whitney U test showed no significant differences in the bacterial numbers found among the different surfaces. The transfer rates of Campylobacter spp. from utensils to cucumber cuts varied from 0% to more than 100%. The bacteria detected could be from the utensils and cucumber contamination before purchase or due to other factors where further investigation is required. The possibility is there for Campylobacter to spread to contact surfaces during chilled broiler handling; therefore, utensils and hands involved should be washed thoroughly especially before ready-to-eat food preparation.